Virus-induced transgene- and tissue culture-free heritable genome editing in tomato - Ye Liu; Trevor Weiss; Jinhee Lee; Jessica Powell; Shi Ying Charlize Choo; Elnaz Roshannai; Maris Kamalu; Jasmine Amerasekera; Suhua Feng; Steven E. Jacobsen (Proceedings of the National Academy of Sciences, 2026)
Genome editing has emerged as a powerful tool for genome manipulation and trait improvement in crops. However, most commonly used approaches rely on tissue culture and transgenic materials, which are time-consuming, labor-intensive, and often strongly genotype-dependent. Here, we developed a Tobacco rattle virus (TRV)-based system to deliver the compact ISYmu1 TnpB endonuclease, coupled with in planta shoot regeneration, to achieve somatic and heritable genome editing across different tomato cultivars without tissue culture. By targeting SlPDS , we successfully generated virus-free homozygous mutant progeny in a single generation. Furthermore, we extended this system to the functional analysis of the previously uncharacterized SlDA1 locus, revealing its involvement in organ size regulation, and recovered transgene-free SlDA1 mutants displaying enlarged fruits. Given the wide host range of TRV, our system should be broadly applicable for rapid, nontransgenic and less genotype-dependent heritable genome editing, thereby advancing both functional genomics and crop improvement.